PERSEPSI PEDAGANG KAKI LIMA TERHADAP KEBIJAKAN PENATAAN KAWASAN TAMAN POCI KOTA TEGAL - Deni Riza Kurniawan; Yuwanto .; Nunik Retno H (Journal of Politic and Government Studies, 2013)
Reasons behind the author in writing this paper that in 2010 the government of Tegal have relocated street vendors in the Poci Park, Tegal, the street vendors were relocated to the field of PJKA which is right in front of the Poci Park. The relocation was based on Regulation No. 3 of 2008 on Street Vendors settings. However, in implementation the policy arise problems, which the place that the vendor selling now was deemed unfit. This is because the shanties of thevendors which mostly semi-permanent is not well ordered, no access roads to the buyer and the absence of electricity in there. The situation is exacerbated by the condition of access roads muddy if it rains. This affects the level of income the vendors who were increasingly losing. Some even forced to sell their shanties. The condition also is encouraging vendors to be selling back in the old place, it also encourages local governments to re-right the situation by confiscating merchandise and carts where they are selling. It also raises a variety of perceptions among the traders about the application of the policies.The purpose of this study was to determine the level of knowledge and perception of Street Vendors to the policy of restructuring the Poci Park area, Tegal. This study uses descriptive type is the type of research that aims to depict or describe the symptoms and analyze the symptoms, using a quantitative approach.The results showed that the level of knowledge the street vendors on policy restructuring the Poci Park area of Tegal is still lacking, it is because not involve street vendors during the making of policy. The perception of street vendors towards restructuring policies the Poci Park area of Tegal is the city government considered carelessly in relocating the street vendors.Keywords: Perception, Policy, street vendors